PENGARUH KONEKSI INTERNET DAN PEMAHAMAN TEKNOLOGI TERHADAP MOTIVASI DALAM MENGIKUTI KEGIATAN DIKLAT DARING PENGUATAN KEPALA SEKOLAH - Indrawan, I Putu Eka; Setiawan, I Made Dedy (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The first online training to strengthen school principals was carried out in Bali by LPD PGRI Mahadewa University Indonesia. This study aims to determine: the effect of an internet connection on the principal's motivation to participate in online principal strengthening training; the influence of technology understanding on the principal's motivation to take part in online school principal strengthening training; as well as the influence of internet connection and shared understanding of technology on the motivation of school principals in participating in online school principal strengthening training. Data were analyzed by statistical multiple regression analysis. The sample in this study were 65 school principals. The results showed that there was a significant effect of internet connection on the principal's motivation. When viewed from the understanding of technology on the principal's motivation also has a significant effect. Taken together, the predictors X1 (Internet connection) and X2 (Understanding Technology) on Y (Motivation) have a significant relationship. This shows that there is a significant relationship between Internet Connection and Understanding of Technology on the Motivation of Principals in Participating in Online School Principal Strengthening Training Activities at LPD PGRI University Mahadewa Indonesia. Based on the results of the analysis and conclusions, it can be suggested to principals to maintain motivation, so that they can become an example for teachers.